A three-phase active rectifier topology for bipolar DC distribution - Junyent,Ferre A; Li,Y; Rodríguez-Bernuz,JM (IEEE Transactions on Power Electronics, 2018)
A new three-phase active rectifier topology is proposed for bipolar dc distribution, which can achieve the independent dc-pole control, with only one two-level voltage source converter and an ac-side grounding inductor. The averaged large-signal model and linearized small-signal model of the rectifier are derived in the stationary reference frame. Moreover, a control system is proposed with proper controller parameters. Besides, the rectifier is tested on an experiment platform. Comprehensive experiment results are given and analyzed to validate the function of the proposed rectifier under different operation conditions, including the rectifier start-up performance, rectifier dynamics with unbalanced dc loads for two poles, and rectifier dynamics with asymmetrical dc voltages for two poles. Finally, the proposed rectifier is compared with other two existing ac-dc conversion approaches, in terms of required number and rating of components as well as power losses with different load imbalance levels, which further highlight some potential benefits of the proposed topology.